Lower vitamin D levels are associated with higher systemic lupus erythematosus activity, but not predictive of disease flare-up. Issue 1 (10th June 2014) - Schoindre, Yoland; Jallouli, Moez; Tanguy, Marie-Laure; Ghillani, Pascale; Galicier, Lionel; Aumaître, Olivier; Francès, Camille; Le Guern, Véronique; Lioté, Frédéric; Smail, Amar; Limal, Nicolas; Perard, Laurent; et al.
Abstract : Objectives: Growing evidence suggests that vitamin D plays a key role in the pathogenesis and progression of autoimmune diseases, including systemic lupus erythematosus (SLE). Recent studies have found an association between lower serum 25-hydroxyvitamin D (25(OH)D) levels and higher SLE activity. We studied the relationship between 25(OH)D levels and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score, and we assessed for the first time the role of vitamin D in predicting SLE flare-ups. Methods: Serum 25(OH)D levels were measured in 170 patients with SLE who were prospectively followed up for 6 months (Plaquenil LUpus Systemic study, ClinicalTrials.gov number NCT00413361 ). Results: The mean SLEDAI score was 2.03±2.43 and 12.3% patients had active disease (SLEDAI ≥6). The mean 25(OH)D level was 20.6±9.8 ng/mL. Deficiency (25(OH)D <10 ng/mL) was observed in 27 (15.9%), insufficiency (10≤25(OH)D<30) in 112 (65.9%) and optimal vitamin D status (25(OH)D≥30) in 31 (18.2%) patients. In multivariate analysis, female gender (p=0.018), absence of defined antiphospholipid syndrome (p=0.002) and higher creatinine clearance (p=0.004) were predictive of lower 25(OH)D levels. In multivariate analysis, lower 25(OH)D levels were associated with high SLE activity (p=0.02). Relapse-free survival rate was not statistically different according to the vitamin D status during the 6-month follow-up (p=0.22). Conclusions: We found a low vitamin D status in the majority of patients with SLE, and a modest association between lower 25(OH)D levels and high disease activity. There was no association between baseline 25(OH)D levels and relapse-free survival rate.